2014
DOI: 10.1016/j.marpolbul.2014.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glyphosate-based herbicide on early life stages of Java medaka (Oryzias javanicus): A potential tropical test fish

Abstract: Glyphosate is globally a widely used herbicide, yet there is little information on their toxicity to marine fishes. Java medaka, a small tropical fish native to coastal areas in several Southeast Asian countries, is viewed as a suitable candidate for toxicity test and thus was used for this study. Java medaka adults were cultured in the laboratory and the fertilized eggs of the F2 generation were exposed to different concentrations of glyphosate-based herbicide (100, 200, 300, 400 and 500 ppm) until they hatch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…The eggs with no visible development (to the naked eye) could have been completely infertile or showing developmental arrest at an early stage. There are multiple potential mechanisms underlying such effects: For example, early embryos of fish showed developmental anomalies (disproportional head and body size) and increased heart rate (medeka, 100-500 mg/L RoundUp 31 , neurotoxic effects zebrafish, up to 50 mg/L RoundUp 32 ) and Xenopus showed craniofacial deformities 12 . Poultry embryos and mice oocytes expressed increased oxidative stress (500 mM pure glyphosate 33 ) and lower hatchability (10 mg/kg egg RoundUp 24 ) in response to GBH exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The eggs with no visible development (to the naked eye) could have been completely infertile or showing developmental arrest at an early stage. There are multiple potential mechanisms underlying such effects: For example, early embryos of fish showed developmental anomalies (disproportional head and body size) and increased heart rate (medeka, 100-500 mg/L RoundUp 31 , neurotoxic effects zebrafish, up to 50 mg/L RoundUp 32 ) and Xenopus showed craniofacial deformities 12 . Poultry embryos and mice oocytes expressed increased oxidative stress (500 mM pure glyphosate 33 ) and lower hatchability (10 mg/kg egg RoundUp 24 ) in response to GBH exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxicity by oxidative stress by Roundup R has been shown by transcriptomic profiling in carp and zebrafish (Uren Webster and Santos, 2015;Sulukan et al, 2017). Acute toxicity, harmful physiological effects including hepatotoxicity, neurotoxicity, deteriorated sperm counts, early life stage development and DNA-damaging effects have been reported for numerous other fish species as well for sublethal exposures to Roundup R products including Roundup Original R , Roundup Transorb R and Roundup WG R , Garlon R , and other glyphosate-based herbicides (Soso et al, 2007;Cavalcante et al, 2008;Guilherme et al, 2010Guilherme et al, , 2014aModesto and Martinez, 2010;Shiogiri et al, 2012;Ghisi and Cestari, 2013;Nwani et al, 2013;Marques et al, 2014;Moreno et al, 2014;Navarro and Martinez, 2014;Richard et al, 2014;Sinhorin et al, 2014;Braz-Mota et al, 2015;Menéndez-Helman et al, 2015;Li et al, 2016;de Moura et al, 2017;Sánchez et al, 2017;Gonçalves et al, 2018;Zebral et al, 2018) or POEA (Yusof et al, 2014). Roundup R was found to disrupt 17β-estradiol and reduce glutathione concentration in the liver of the endangered fish species delta smelt (Hypomesus transpacificus) upon 6 h of exposure at levels corresponding to 78 µg/l glyphosate concentrations and above (Jin et al, 2018).…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%
“…This small tropical fish has been widely used as a test organism in toxicology and ecotoxicology studies (2)(3)(4)(5). This species has also been used in several studies to represent marine and freshwater fish due to its ability to occupy fresh, brackish, and saltwater (6).…”
Section: Introductionmentioning
confidence: 99%
“…In the natural environment, a study found that the mean pH of O. javanicus habitats (6.60 ± 0.40) tends to be higher compared to that of the Indian medaka O. dancena (5.9 ± 0.22), along the west of Peninsular Malaysia, Malaysia (7). However, for culture and breeding conditions in the laboratory, a pH range of 5.5-5.6 was used in an experimental study for O. javanicus (5), while for the Japanese medaka (O. latipes), a pH range between 6.8 and 7.5 was recommended for large-scale breeding (11).…”
Section: Introductionmentioning
confidence: 99%